Marine Suitability Assessment for Mariculture: Combining GIS and AHP Technique in Dampier Strait Conservation Area, West Papua Province, Indonesia - Ichsan Suryo Wibowo; Ali Mashar; Niken Tunjung Murti Pratiwi; Fery Kurniawan (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Mariculture is one of the activities that can pressure the aquatic environment. Mariculture activities are carried out by considering the sustainability aspects of environmentally friendly implementation. The suitability of the location for mariculture activities refers to the geographical and hydro–oceanographic conditions seen from the waters' physical, chemical, and biological parameters. The suitability index produced using multiple approaches (GIS-based AHP) can be used to determine the potential locations for mariculture development.   Abstract Potential mariculture activities in the Dampier Strait Conservation Area, which are indicated by the availability of water space and local commodities, can have a multiplier effect on socio-ecological aspects. Therefore, reasonable development steps are needed to carry out environmentally friendly aquaculture. This study aims to determine the potential use of water space for the development of mariculture activities based on the level of suitability using multiple approaches. Suitability analysis was carried out with Geographic Information System (GIS) based on the Analytical Hierarchy Process (AHP) by considering the area's characteristics using several aspects seen from the geographical conditions and water quality (physical, chemical, and biological). Based on the suitability analysis results, the potential water space that can be used for mariculture development activities, namely seaweed and pearl oyster cultivation was 1,130.45 ha (0.49% of the overall space allocation 232,588.59 ha). A justification was then carried out to determine a suitable location in terms of its accessibility and environmental friendliness. The analysis has shown promising results in determining potential locations for developing mariculture activities for seaweed and pearl oyster commodities based on sustainable and environmentally friendly cultivation.